Long Standing Foreign Body Oesophagus Masquerading Bronchial Pneumonia: A Case Report (Tanzania Medical Journal, 2023)
Foreign bodies in the oesophagus can be unrecognised by parents/caregivers and health care providers especially when there is no clear history. Depending on the stage of developmental milestones, children explore the environment and can ingest foreign bodies which cannot be clear to the parents/caregivers and health care providers especially when it presents with vague symptoms. This case report describes a 2 year-old female child who presented with mild cough, poor feeding and on and off irritability associated with excessive crying for 3 weeks. The Chest x-ray revealed oesophageal foreign body. This case showed that the foreign body was missed and instead the child was treated as a case of bronchial pneumonia.